2012
DOI: 10.1111/j.1538-4616.2011.00470.x
|View full text |Cite
|
Sign up to set email alerts
|

The Taylor Rule and Forecast Intervals for Exchange Rates

Abstract: In this paper, we examine the Meese-Rogoff puzzle from a different perspective: out-of-sample interval forecasting. While most studies in the literature focus on point forecasts, we apply semiparametric interval forecasting to a group of exchange rate models. Forecast intervals for 10 OECD exchange rates are generated and the performance of the empirical exchange rate models are compared with the random walk. Our contribution is twofold. First, we find that in general, exchange rate models generate tighter for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 78 publications
(93 reference statements)
0
10
0
Order By: Relevance
“…Consequently, a number of studies have shown that the Taylor rule model has better performance in the expectation of exchange rate determination than random walk model (see for example Molodtsova and Papell, 2009;Wilde, 2012;Ince, et al 2016;Wang, et al 2016;Byrne, et al 2016;Ince, et al 10 2016). Commenting on the recent studies, Wang and Wu (2012) in a study of OECD countries show that the Taylor rule model is significantly better in the expectation of exchange rate dynamics than the random walk model. Ince, et al (2016) evaluates the short-run out-of-sample predictability for the exchange rates of eight different currencies against the US dollar and find strong evidence in favour of the Taylor rule model compared to the random walk model.…”
Section: A Review Of the Literature On Exchange Rate Forecastingmentioning
confidence: 99%
“…Consequently, a number of studies have shown that the Taylor rule model has better performance in the expectation of exchange rate determination than random walk model (see for example Molodtsova and Papell, 2009;Wilde, 2012;Ince, et al 2016;Wang, et al 2016;Byrne, et al 2016;Ince, et al 10 2016). Commenting on the recent studies, Wang and Wu (2012) in a study of OECD countries show that the Taylor rule model is significantly better in the expectation of exchange rate dynamics than the random walk model. Ince, et al (2016) evaluates the short-run out-of-sample predictability for the exchange rates of eight different currencies against the US dollar and find strong evidence in favour of the Taylor rule model compared to the random walk model.…”
Section: A Review Of the Literature On Exchange Rate Forecastingmentioning
confidence: 99%
“…Moreover, empirical evidence in favor of predictive ability of macroeconomic fundamentals has been mainly found at longer horizons (Engel et al, 2007). Cheung et al (2005) conclude that models with macroeconomic fundamentals cannot outperform the random walk and only models with Taylor rule fundamentals can have some predictive merit (Molodtsova and Papell, 2009;Wang and Wu, 2012).…”
Section: Introduction and Literaturementioning
confidence: 99%
“…They find evidence that an interest rate reaction function in the form of a Taylor rule works particularly well. Similarly, Wang and Wu (2012) report that in their analysis of a group of exchange rate models for 10 OECD countries, the Taylor rule performs best empirically as a monetary policy rule. Taylor (2001) generally discusses the role of the exchange rate in monetary policy rules.…”
Section: Introductionmentioning
confidence: 99%